Exploring the Interplay of Supply Chain Integration and Resilience in State-Owned Logistics Enterprise in Namibia, Port of Walvis Bay - SHOOYA, Anatolia Tshanyengandje; MBHELE, Patmond Thokozani (International Journal of Environmental, Sustainability, and Social Science, 2026)
Abstract: This article delves into the intricate dynamics of supply chain integration and resilience within a state-owned logistics enterprise in Namibia, specifically focusing on the Port of Walvis Bay. A quantitative research design was adopted to provide a comprehensive understanding of how supply chain integration practices impact the resilience of this strategic logistics hub. The Port of Walvis Bay is a vital gateway for Namibia's international trade, and its ability to adapt to disruptions and maintain operational efficiency is of utmost importance. To achieve this objective, the correlational approach is necessary for establishing the association between supply chain integration and resilience in state-owned logistics enterprises. A combination of probability and non-probability sampling techniques was adopted in administering 370 questionnaires to six logistics industries associated with the port of Walvis Bay, and statistical analysis. The study seeks to explore the extent to which various dimensions of supply chain integration, such as information integration, internal integration, customer integration, and supply integration, influence the resilience of the logistics enterprise. It was found that strategies to enhance the resilience of state-owned logistics entities ultimately contribute to the overall efficiency and competitiveness of the Port of Walvis Bay and, by extension, Namibia's logistics sector. The managerial relevance of the current study was drawn from the statistical inverse relationship between supply chain integration and resilience in Namibia's logistics enterprises.